Corrosion of Metals Modified with Formulations Based on Organosilanes - Maxim Petrunin; Tatyana Yurasova; Alevtina Rybkina; Liudmila Maksaeva (Metals, 2023)
Methods for preliminary modification of the surface of structural metals with formulations based on organosilanes, including both solutions of individual organosilanes and two-component mixtures consisting of two organosilanes or an organosilane with an organic corrosion inhibitor, have been developed. As a result of this modification, a self-assembling siloxane polymeric/oligomeric nanoscale layer is formed on the metal surface. Such layers are capable of changing the physicochemical properties of the metal surface, in particular reducing the susceptibility of the metal to corrosive destruction. In this work, the mechanism of formation of organosilicon nanolayers and their effect on the electrochemical and corrosion behavior of metals have been studied in detail by a set of electrochemical methods, while laboratory studies and accelerated corrosion tests of carbon steel and zinc, modified with formulations based on organosilanes, have been carried out. The greatest inhibitory effect is demonstrated by two-component modifying formulations, namely mixtures of vinyl with aminosilane and vinylsilane with benzotriazole. The mechanism of corrosion inhibition by surface nanolayers formed upon surface modification with two-component mixtures has been considered.